Pelatihan Keterampilan Pembelajaran Berbasis Masalah bagi Guru SMAN 1 Sakra Timur - Hadi Gunawan Sakti; Rudi Hariawan; M. Zainal Mustamiin (Jurnal Pengabdian UNDIKMA, 2020)
The learning system that is still teacher-centered makes teachers play an active role more than students, even though the object of this learning itself is students so that the impact on student achievement is still low. Therefore, we need a method that is able to invite students to play an active role, one of the skills tested is problem-based learning skills, in this training teachers are expected to be more optimized in the application of cooperative learning to improve student learning activities and achievement in SMAN 1 Sakra Timur. This training activity is carried out through several methods of implementation, namely: 1) Coordination of activities, 2) Preparation of tools and materials, 3) Implementation in the field. The results of this community service activity are that teachers as trainees are highly motivated in these activities and teachers have the understanding and ability to apply problem-based learning skills well.